Effect of Guided Inquiry Learning Model Through Ice Cream-Making Experiments on Students Higher Order Thinking Skills (HOTS) - Arinda Salsabila Putri; Fitria Wulandari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Developing Higher Order Thinking Skills (HOTS) has become an important focus in elementary science education because students are expected not only to understand concepts but also to analyze, evaluate, and create solutions to real-life problems. This study aims to examine the effect of a guided inquiry learning model implemented through ice cream-making experiments on the Higher Order Thinking Skills (HOTS) of fourth-grade elementary school students. The research employed a quantitative approach with a nonequivalent control group quasi-experimental design. The participants were 53 fourth-grade students, including 25 in the experimental class and 28 in the control class. The experimental class received guided inquiry-based experimental learning, while the control class was taught using conventional methods. Students' higher-order thinking skills were assessed using essay exams that focused on three areas of advanced thinking: analyzing, evaluating, and creating. These tests were given before and after the learning period to measure progress. The data were checked for normality and homogeneity before conducting the independent-samples t-test. The results showed that the data followed a normal distribution and had similar variability, meeting the requirements for hypothesis testing. The t-test results showed a very low significance value of 0.000, which is less than 0.05. This indicates a significant difference in HOTS scores between the treatment and control groups. The experimental group scored higher, on average, in HOTS (88.10) than the control group (77.86). The average difference of 10.24 points shows a big improvement in the experimental group's ability to think critically and solve complex problems. The results show that using the guided inquiry learning method with ice cream-making experiments helps students improve their higher-order thinking skills in a meaningful way. Therefore, guided inquiry-based experiments can be an effective and relevant way to help students develop higher-order thinking skills in elementary science classes.